Driving forces of labour migration as barriers to labour migrants' professional mobility: The case of Yugoslav labour migration - Mato Bosnjak (CES Working Papers, 2023)
After consolidation following the Second World War, the Yugoslav regime began modernising the country and transforming means of production, which resulted in a fragile economy and increasing labour surplus. The reforms coincided with economic development and increasing demand for migrant workers in several countries in the western hemisphere. Consequently, the migration of Yugoslav labour emerged and expanded for more than a decade. This article discusses developments conditioning and sustaining Yugoslav labour migration and Yugoslav workers' labour market performance in industrial countries of Western Europe. This article draws on empirical literature and theoretical understandings of labour migration merged with the perception of temporariness of labour migrants' relocation. The article argues that Yugoslav workers' labour market performance in Western Europe was an outcome of interactions between driving forces of Yugoslav labour migration, practices of its main agents, and the surrounding socioeconomic contexts.
Keywords: 330; labour market mobility; professional stagnation; occupational distribution; professional subordination; Yugoslavia